In situ growth of binder-free CNTs@Ni–Co–S nanosheets core/shell hybrids on Ni mesh for high energy density asymmetric supercapacitors. Issue 22 (23rd May 2016) - Peng, Tianquan; Yi, Huan; Sun, Peng; Jing, Yuting; Wang, Ruijing; Wang, Huanwen; Wang, Xuefeng
Abstract : A facile two-step method has been developed to synthesize 3D core/shell-structured composites (CNTs@Ni–Co–S) composed of ternary nickel cobalt sulfide nanosheets (Ni–Co–S) as the shell and carbon nanotubes (CNTs) as the core on a flexible Ni mesh (Ni@CNTs@Ni–Co–S). Abstract : A facile two-step method has been developed to synthesize 3D core/shell-structured composites (CNTs@Ni–Co–S) composed of ternary nickel cobalt sulfide nanosheets (Ni–Co–S) as the shell and carbon nanotubes (CNTs) as the core on a flexible Ni mesh (Ni@CNTs@Ni–Co–S). CNTs are in situ grown on a metallic Ni mesh via a chemical vapor deposition (CVD) method and further serve as the skeleton to deposit ultrathin Ni–Co–S nanosheets. Due to the intimate combination of highly conductive CNTs and high redox-active Ni–Co–S nanosheets, the as-prepared composite electrode delivers a high specific capacity of 222 mA h g −1 at 4 A g −1 and excellent rate capability (193 mA h g −1 at 50 A g −1 ). An advanced asymmetric supercapacitor (ASC) was designed using Ni@CNTs@Ni–Co–S as the positive electrode and carbon cloth @CNTs as the negative electrode in KOH solution. Our ASCs present a high energy density of 46.5 W h kg −1 at a power density of 800 W kg −1 . Even at an ultra-high power density of 33.7 kW kg −1 (charging only for 2 s to 1.6 V), the ASCs can still demonstrate an energy density as high as 15.9 W h kg −1 . Impressively, when charging to 3.4 V within 70 s, two ASCs assembled in series can effectively light up 10 light-emitting diodes (LEDs, lowest working voltage are 3.2 V) for more than 2 min or one single LED for around 50 min. These remarkable capacitive performances of Ni@CNTs@Ni–Co–S//CC@CNTs ASCs show great potential for application in supercapacitors, particularly in wearable devices.